Abyssinia at al-Azhar: Muslim Students from the Horn of Africa in Late Medieval Cairo - (:unkn) unknown (My University, 2019)
At the end of the fifteenth century, Muslim students from the Horn of Africa would come to Cairo in their search for knowledge and to dwell in the venerable mosque of al-Azhar. They formed a significant community of foreign students in the Egyptian metropolis, to the extent that they enjoyed their own fraternity where they gathered along their fellow countrymen. The article investigates the gradual development in Cairo of a Muslim community originating from the Horn of Africa. It puts their sudden visibility in the context of the establishment of the first student fraternities in al-Azhar's history. Finally, it questions their role in the growing connections between Egypt and the Horn of Africa in the later Middle Ages.
Keywords: African Research